2003
DOI: 10.1577/1548-8659(2003)132<0196:psoasi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Atlantic Salmon in Maine with Reference to Populations from Atlantic Canada

Abstract: Anadromous Atlantic salmon Salmo salar from 12 rivers in Maine, 3 rivers in New Brunswick, and 2 rivers each in Nova Scotia, Quebec, Newfoundland, and Labrador as well as 2 landlocked strains in Maine (N ϭ 3,863) were genotyped at 11 microsatellite loci. Fish in the drainages of Maine's Kennebec and Penobscot rivers were genetically similar to those sampled from the 8 rivers recently listed as containing an endangered distinct population segment under the United States' Endangered Species Act. Genetic distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 33 publications
3
28
0
3
Order By: Relevance
“…Given that 95.6% of returning Dennys river salmon from 1947-1994 were 2-Sea-Winter individuals (Baum 1997), generation length (t) may be assumed to be roughly 4 years. However, parentage attributable to precocious male parr has been shown to have a strong effect on such estimates (Spidle et al 2003), and it has been suggested that precocious parr may compensate for decreased numbers of anadromous spawners (Martinez et al 2000). Although there is no a priori information about the proportion of successfully breeding precocious parr in this population, it is reasonable to assume that, if present, it would reduce the generation length.…”
Section: Effective Population Sizementioning
confidence: 93%
See 3 more Smart Citations
“…Given that 95.6% of returning Dennys river salmon from 1947-1994 were 2-Sea-Winter individuals (Baum 1997), generation length (t) may be assumed to be roughly 4 years. However, parentage attributable to precocious male parr has been shown to have a strong effect on such estimates (Spidle et al 2003), and it has been suggested that precocious parr may compensate for decreased numbers of anadromous spawners (Martinez et al 2000). Although there is no a priori information about the proportion of successfully breeding precocious parr in this population, it is reasonable to assume that, if present, it would reduce the generation length.…”
Section: Effective Population Sizementioning
confidence: 93%
“…Pooling temporally separated samples to increase sample sizes is standard practice when spawning events involve individuals of different ages Spidle et al 2001;Spidle et al 2003), and has been recommended for species with overlapping generations when populations are small and the potential effects of drift are large (Waples 1990). To increase the sample size of our $1975 sample, we pooled individual returning salmon obtained from 1974-1976.…”
Section: Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…The different areas of the river appear to contain distinct sub-populations (significant F ST values), with migration between them (M values) but exhibiting significant spatial population structuring, which is temporally stable and comprising at least two well differentiated units (upstream and downstream) and a mixture in the rest of the drainage. This differs somewhat with the suggestion of the existence of a metapopulation linking neighbouring rivers in this region proposed by Ayllon et al (2006) and Kuparinen et al (2010), revealing for the first time the occurrence of fine population structuring at the within river level in northern Spain, as has been described for Atlantic salmon at other latitudes (Ståhl, 1983;Heggberget et al, 1986;Verspoor and Jordan, 1989;Hurrell and Price, 1993;Garant et al, 2000;Spidle et al, 2003;Vähä et al, 2007;Primmer et al, 2006;Dillane et al, 2008). As already proposed by other authors (Garcia-Vazquez et al, 1991;Vespoor, 1997) stocking with foreign fish should be discarded as a method for restoration and enhancement of this Atlantic salmon population.…”
Section: Figurementioning
confidence: 57%